Pomżesz obliczyć?
Przykład: -(+273)+(-50)-(-961)-48=-237-50+961-48=961+[-(273+50+48)]=961+(-371)=(961-371)=590
a) -(+41)+36-(-138)+(-312)=
b) +(-372)-(+257)+468-(-15)=
c) -952-(+99)-(+60)-(-278)=
d) +(+926)-(+21)+(-62)+156=
e) -(+354)-(-45)+(-608)-70=
f) -186-(-586)-(+34)+(+37)=
g) +(+48)+(-202)+390+(+41)=
h) -(-225)+(+850)-(+76)-49=
i) +14+(+793)+(-12)-(202)=
j) -(-59)-(+53)+337+(-491)=
k) -(+90)+143+(+84)-(+518)=
l) +(+832)-(+67)-356-(+589)=
prosze mam to na jurto...:)

1

Odpowiedzi

2010-02-07T16:22:33+01:00
A) -(+41)+36-(-138)+(-312)= -41+36+138 - 312 =-179
b) +(-372)-(+257)+468-(-15)=-372-257 +468+15 = -146
c) -952-(+99)-(+60)-(-278)=-952 - 99 - 60 + 278 = -833
d) +(+926)-(+21)+(-62)+156= 926 -21 - 62 +156 = 999
e) -(+354)-(-45)+(-608)-70=-354 + 45 - 608 - 70 = -987
f) -186-(-586)-(+34)+(+37)= -186 + 586 - 34 + 37 = 403
g) +(+48)+(-202)+390+(+41)=48 - 202 + 390 + 41 = 277
h) -(-225)+(+850)-(+76)-49=225 + 850 - 76 - 49 = 950
i) +14+(+793)+(-12)-(202)=14 + 793 - 12 - 202= 593
j) -(-59)-(+53)+337+(-491)= 59 - 53 + 337 - 491 = -148
k) -(+90)+143+(+84)-(+518)= -90 + 143+ 84 - 518 = -381
l) +(+832)-(+67)-356-(+589)= 832 - 67 - 356 - 589 = -180